Career Growth Potential: Examining the Roles of Political Skill, Social Resource Acquisition, and Ingratiation - Akmal Akmal; Elfitra Azliyanti (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2026)
This study examines the effects of political skill on career growth potential through social resource acquisition and the moderating role of ingratiation among civil servants. Drawing on Social Resource Theory, the study proposes that politically skilled employees are better able to acquire valuable social resources, thereby enhancing their career growth potential. A quantitative approach was employed using purposive sampling, involving 137 civil servants from the West Sumatra Provincial Government. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results indicate that political skill has a positive and significant effect on both social resource acquisition and career growth potential. Social resource acquisition also positively influences career growth potential. However, ingratiation has no significant direct effect on career growth potential and does not significantly moderate the relationship between social resource acquisition and career growth potential. These findings suggest that interpersonal competence and access to valuable social resources are more important determinants of career growth than ingratiation behavior. This study contributes to the career development literature by extending Social Resource Theory and provides practical implications for public organizations in promoting career advancement through the development of employees' political skills and workplace social resources.